An Insight into the Increasing Role of LncRNAs in the Pathogenesis of Gliomas - Yan, Yuanliang; Xu, Zhijie; Li, Zhi; Sun, Lunquan; Gong, Zhicheng (Frontiers in Molecular Neuroscience, 2017)
LncRNAs (long non-coding RNAs) are essential epigenetic regulators with critical roles in tumor initiation and malignant progression. However, the roles and mechanisms of aberrantly expressed lncRNAs in the pathogenesis of gliomas are not fully understood. With the development of deep sequencing analyses, an extensive amount of functional non-coding RNAs has been discovered in glioma tissues and cell lines. Additionally, the contributions of several lncRNAs, such as Hox transcript antisense intergenic RNA (HOTAIR), H19 and Colorectal neoplasia differentially expressed (CRNDE), previously reported to be involved in other pathogenesis and processes to the oncogenesis of glioblastoma (GBM) are currently addressed. Thus, lncRNAs detected in tumor tissues could serve as candidate diagnostic biomarkers and therapeutic targets for gliomas. To understand the potential function of lncRNAs in gliomas, in this review, we briefly describe the profile of lncRNAs in human glioma research and therapy. Then, we discuss the individual lncRNA that has been under intensive investigation in glioma research, and the focus is its mechanism and clinical implication.